Engineering Education in the Context of Digitalization and Transition to a Green Economy (SYNERGY 2022 Conference Results Review) - M. F. Galikhanov; V. V. Kondratyev; I. G. Akhmetov; G. R. Ganieva (Moscow Polytechnic University, 2022)
The article summarizes the results of the plenary session of the international network conference "Engineering education in the context of digitalization and transition to a green economy - SYNERGY-2022" held at the Nizhnekamsk Chemical Technology Institute of Kazan National Research Technological University from October 13 to 14, 2022. The forum was devoted to the training of engineers in the conditions of digitalization and the transition to a green economy. It brought together representatives of universities and industrial enterprises of Russia and abroad. Among the participants were representatives of national research universities and supporting universities of PJSC Gazprom, state authorities and industrial enterprises of Tatarstan. It was possible to observe the work of the plenary session in real time via the Internet in all the main universities of Gazprom. The organizers of the event were the Ministry of Science and Higher Education of the Russian Federation, the International Society for Engineering Pedagogy (IGIP), the Association of Engineering Education of Russia (AEER), as well as the Ministry of Industry and Trade of the Republic of Tatarstan and the Kazan National Research Technological University. Gazprom PJSC was the general sponsor. In total, the conference gathered more than 200 participants (120 online and 80 in person) from 15 universities in Russia, Germany and Kazakhstan. Representatives of 12 industrial enterprises spoke, 42 reports were made.